Peran kepala sekolah dalam pengelolaan perpustakaan untuk mendukung pembelajaran di masa pandemi COVID-19 - Setiawan Setiawan; Syihabuddin Qalyubi; Nurdin Laugu (Berkala Ilmu Perpustakaan dan Informasi, 2023)
Introduction. This research is to examine perspectives of teachers, students and librarians toward leadership roles regarding information technology development in school libraries in supporting learning in the era of the COVID-19 pandemic. Data Collection Methods. This study used a quantitative descriptive approach with 100 respondents. The sampling technique used the probability sampling with simple random sampling method. Results and Discussion. The role of school leaders in developing library governance has not yet been significant so that libraries could not contribute effectively to the learning process. During the pandemic, the role of IT is needed by teachers and students, particularly for the library users to finish their assignment from home. Users also need to have the library updates regarding books. Many teachers and students do not understand how to use of information technology in the library including how to access or search information (online). Conclusion. School leaders play an active role in improving the quality of the library as a source of learning to create benefits for the school community. The discussion on the abnormal situation leadership among school leaders.